A prospective study to investigate the epidemiology of various gynaecological problems among women at a tertiary care centre - Thiyagarajan, Kamalpriya; Chaudhari, Vaishali; Patil, Yogini; Shah, Kshama; Gawali, Vijaykumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Women have unique health concerns and are affected by health issues that are either more prevalent in women than in men or a disease that is common in men too but require a different treatment approach in women and this is where women’s health comes into play. Women are afflicted by some or the other reproductive morbidity at least once in their lifetime. These reproductive morbidities are broadly categorised into obstetric, gynaecological or contraceptive morbidity. Among these three categories of reproductive morbidities, gynaecological morbidities are relatively more frequent and account for a major proportion (43%-92%) of the disease burden in women. Methods: This study was a prospective, single-centre, controlled, observational study conducted from January 2021 to December 2021 in the department of obstetrics and gynaecology of Bhaktivedanta hospital and research institute, Thane, India. The objective of this study was to study the magnitude and impact of a particular type of gynaecological problem in this region and to know the need of developing better preventive and therapeutic protocols including the start of specialised gynaecological clinics. Results: Among various reproductive health issues, there were three most frequently occurring issues reported which were menstrual disorder, abnormal vaginal discharge and lower abdominal pain with a frequency of 29%, 24% and 19% respectively. Among the menstrual disorders commonly observed in women, the most common disorders were irregularity of menstrual cycles (39%) and menorrhagia (31%). Out of all the characteristics of vaginal discharge, changes in its colour constituted the highest percentage (51%) with white and yellow colour discharge being the most common (23% and 24% respectively). Conclusions: Menstrual irregularities and reproductive tract infections were the major gynaecological morbidities observed. This study identifies major gynaecological problems and highlights the need for dovetailing health care resources towards it.